Transport in perfluorosulfonic acid (PFSA) membranes: effects of pretreatment, side-chain length, and alkali metal cation - Castro, Sebastian; Ssekimpi, Dennis; Tang, Youneng; Hallinan, Daniel (Frontiers in Membrane Science and Technology, 2025)
This work investigates the effects of pretreatment, side-chain length, cation type, and the interplay between them on transport properties in the commercial PFSA membranes, Nafion 115 and Aquivion E98-09S. Solutions of 1M LiCl, NaCl, and KCl were used to measure permeability, water uptake, salt partitioning, and conductivity in these membranes. We find that membrane pretreatment can make a one or two order of magnitude difference in permeability and in turn shift the selectivity towards higher-mobility salts. Conversely, in the as-received state, the membranes have lower water contents and cation hydrated radius plays a greater role than ion mobility. This results in as-received membranes exhibiting selectivity for lithium over sodium. These findings challenge the paradigm established by the body of fuel cell literature, indicating that although pretreatment increases water uptake and ionic conductivity in PFSA membrane, it may not be beneficial in applications that require selective ion transport, such as for harvesting minerals from desalination brine or as separators in redox flow batteries. In other words, ion transport through membranes can be made significantly different from that in aqueous solution by minimizing water uptake so that membrane morphology plays a dominant role.